A rare case of physical dependence with psychedelic LSD - A case report. (4th July 2019) - Modak, Tamonud; Bhad, Roshan; Rao, Ravindra
ABSTRACT: Lysergic acid diethylamide (LSD) is a semisynthetic compound with strong psychoactive properties. LSD has been used as an adjunct to psychotherapy and treatment for various forms of drug addiction as well as a drug of abuse by the hippie counterculture movement of the 1960s. The literature regarding LSD is limited, and it has hardly been studied after it was banned in the 1970s. LSD is known to cause psychological dependence, but physical dependence on LSD is unknown. Continuous use of LSD is also unknown. We describe a case where the person used LSD continuously for a period of two years as his primary drug. He developed a craving, and tolerance to LSD and contrary to known literature the tolerance did not disappear rapidly on discontinuation. Additionally, he developed both physical and psychological symptoms on discontinuing LSD – a factor responsible for continued use. To the best of our knowledge, this is the first report of physical dependence to LSD.